GUNS BEFORE POLITICS - Moorcroft, P.L. (Scientia Militaria - South African Journal of Military Studies, 2012)
’What we must stop is a situation where the gun is a means of promotion, a machine gun a way of applying pressure, a tank becomes government policy.’ This was the despairing cry of an African lawyer during yet another recent military intervention in that most coup-ridden of African states, Dahomey.